Histological features of symptomatic carotid plaques in relation to age and smoking: the oxford plaque study. - Redgrave, J; Lovett, J; Rothwell, P (2010)
BACKGROUND AND PURPOSE: Rates of incident and recurrent cardiovascular events rise steadily with age, due partly to more extensive atherosclerotic burden. However, in patients with similarly severe symptomatic carotid stenosis, increasing age is associated with a greater risk of ipsilateral ischemic stroke. This effect may be due to age-related differences in the pathology of symptomatic carotid plaques. However, previous studies of plaque pathology in relation to age have not accounted for potential confounders, particularly smoking, which is often less prevalent in the elderly population undergoing endarterectomy. Method-We related patient age (<55, 55 to 64, 65 to 74, 75+ years) and smoking habit (never, exsmoker, recent smoker, and current smoker; and number of cigarettes smoked per day) to detailed histological assessments of 526 carotid plaques from consecutive patients undergoing carotid endarterectomy for symptomatic carotid stenosis. RESULTS: Three hundred seventy-nine (72.1%) patients were male (mean/SD age 66.6/8.7). Current/recent smokers were on average 7 years younger at carotid endarterectomy than ex-/never smokers (P<0.001), and age at carotid endarterectomy decreased with increasing number of cigarettes smoked per day (P trend=0.005). Plaques from current/recent smokers had a lower prevalence of intraplaque hemorrhage (P -trend=0.01), but histology was otherwise similar to that in ex-/never smokers, and both groups showed similar changes with age. With increasing age, plaque calcification and large lipid core increased (P<0.001 and P=0.01, respectively) and fibrous tissue (P=0.01) decreased, but lymphocyte infiltration of the plaque (P=0.03) and cap (P=0.002) and overall plaque inflammation (P=0.03) also decreased such that overall plaque instability was unrelated to age. CONCLUSIONS: Smoking is associated with a lower age at carotid endarterectomy suggesting that it may accelerate the development and/or progression of atherosclerosis. However, the mechanisms of plaque instability seem largely unrelated to smoking. Plaques from younger patients had greater inflammatory cell infiltration, whereas those from older patients had a larger lipid core, but there were no age trends in overall plaque instability suggesting the increased risk of stroke in the elderly with symptomatic carotid stenosis is due to other factors.